Upward elevational shift of the Horned Lark (Eremophila alpestris) in alpine breeding sites at Dovrefjell, central Norway - Østvold, Oscar; Dale, Svein; Brevig-Edfeldt, Axel (Ornis Norvegica, 2024)
Climate change is expected to force species to move upwards and polewards. Mountain species are at particular risk because upward elevational shifts may be limited by the maximum height of mountain ranges. The Horned Lark Eremophila alpestris breeds in the high mountains of southern Norway. Two previous studies recorded the elevation of breeding territories of Horned Larks in two regions of Dovrefjell, central Norway. In mountains around Grimsdalen (Dovre municipality) territories had a mean elevation of 1329 m (range = 1200–1450 m, n = 15) in 1969, and in mountains around Einunndalen (Folldal and Oppdal municipalities) the mean was 1339 m (range = 1240–1430 m, n = 15) in 1992. The same mountain areas were resurveyed 30–53 years later in 2022. In Grimsdalen, mean elevation of lark territories was now 1426 m (range = 1260–1570 m, n = 23) and in Einunndalen 1415 m (range = 1196–1523 m, n = 42). Overall, the data suggested a mean upward elevational shift of 2.2 m/year. The shift in elevation suggests that climate change has influenced the elevational range of the Horned Lark in the mountains of central Norway, with potential population consequences if the upward shift continues.